2010
DOI: 10.1007/s11104-010-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

Vertical patterns of fine root biomass, morphology and nitrogen concentration in a subalpine fir-wave forest

Abstract: To clarify the nutrient acquisition strategies for below-ground resources in a subalpine Abies forest with shallow soils, we examined the vertical patterns of fine root biomass, morphology, nitrogen concentration of fine root tissue and soil chemical characteristics in nine quadrats of sapling, young and mature stands in a subalpine fir-wave forest, central Japan. The community characteristics changed with stand development, but stand development did not influence the vertical pattern of fine root characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In the Chinese fir plantation, the SRL remained relatively stable. In contrast, root tissue density, which was considered as an indicator for root functional status [48], showed high variations. The root tissue density increased consistently with stand age.…”
Section: Fine Root Morphologymentioning
confidence: 92%
“…In the Chinese fir plantation, the SRL remained relatively stable. In contrast, root tissue density, which was considered as an indicator for root functional status [48], showed high variations. The root tissue density increased consistently with stand age.…”
Section: Fine Root Morphologymentioning
confidence: 92%
“…In this paper, soil nutrient decreased with the increase of soil depth. High nutrient availability made fine roots concentrate in the soil surface layer (Ugawa et al, 2010), which would impact enzyme activities and microorganism distribution pattern in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…As also mentioned in the root carbon section, fine roots have fresh and young matter with less lignin, and less carbon content can be decomposed easily by increasing the C/N ratio. Similarly, Dicus and Dean (1999) and Ugawa et al (2010) indicated the importance of the nitrogen concentration of fine roots. Interestingly, Ugawa et al (2010) and Noguchi et al (2005) reported that the nitrogen concentration of fine roots and root biomass was higher in surface soils than deep soil layers.…”
Section: Root Nitrogenmentioning
confidence: 93%
“…Similarly, Dicus and Dean (1999) and Ugawa et al (2010) indicated the importance of the nitrogen concentration of fine roots. Interestingly, Ugawa et al (2010) and Noguchi et al (2005) reported that the nitrogen concentration of fine roots and root biomass was higher in surface soils than deep soil layers. We detected the similar result as Ugawa et al (2010) and Noguchi et al (2005) reported, respectively.…”
Section: Root Nitrogenmentioning
confidence: 93%